2023
DOI: 10.1111/camh.12647
|View full text |Cite
|
Sign up to set email alerts
|

Debate: Don't mind the gap – why do we not care about the gender gap in common mental health difficulties?

Abstract: There is a substantial gender gap in common mental health difficulties such as depression and anxiety, and evidence on drivers of this gap is sparse. Yet, the current tendency in the field is to treat it as inevitable, and its drivers are rarely examined as a worthwhile question to pursue. We discuss possible reasons for this oversight, while highlighting the need to reform research priorities and systems to ensure this issue receives the investment and interest necessary to inform better prevention and suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The impact of trauma can be missed if there is too much focus on biological models of experiences such as voice hearing (McCarthy‐Jones et al., 2015). Patalay and Demkowicz (2023) articulate how the responsibility for protection from unwanted sexual attention, preventing harassment and developing skills to cope with oppression often falls on girls and young women, against a backdrop of victim blaming and the stress of constant vigilance. Let us not replicate this unfair burden in health services.…”
Section: Understanding Psychosis‐like Symptoms In the Context Of Gend...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of trauma can be missed if there is too much focus on biological models of experiences such as voice hearing (McCarthy‐Jones et al., 2015). Patalay and Demkowicz (2023) articulate how the responsibility for protection from unwanted sexual attention, preventing harassment and developing skills to cope with oppression often falls on girls and young women, against a backdrop of victim blaming and the stress of constant vigilance. Let us not replicate this unfair burden in health services.…”
Section: Understanding Psychosis‐like Symptoms In the Context Of Gend...mentioning
confidence: 99%
“…Patalay and Demkowicz (2023) highlight the gender gap in common mental health problems and the dearth of evidence on the causes of this gap. We agree with the authors that developing a greater understanding of gender differences and why the research community seem so accepting of reductionist explanations is essential to address existent inequalities.…”
mentioning
confidence: 99%
“…The debate in our current issue arguably highlights one of the most important inequalities internationally, namely the gender gap in mental health. Patalay and Demkowicz (2023) argue that there is a substantial gender gap in common mental health problems such as depression, and evidence on the drivers of this gap is sparse. The gender difference in depression has been long established, and international data have shown that the impact of COVID-19 has disproportionately affected the emotional health of younger women and girls (COVID-19 Mental Disorders Collaborators, 2021); however, according to Patalay and Demkowicz, there remains a pervasive disinterest in the research community and from policy makers of this large inequality.…”
mentioning
confidence: 99%
“…
Drs. Patalay and Demkowicz (2023) offer an impassioned plea for greater attention to be paid to the "gender gap in mental health outcomes" and throw down the gauntlet to the research community to defend its "pervasive disinterest" in this topic. They focus on the gender gap in depressive disorders; the approximately 2 to 1 rate of females to males in prevalence rates, which has been well established (e.g., Hartung & Lefler, 2019).
…”
mentioning
confidence: 99%